When Students Fight Corruption: A Portrait of Anti-Corruption Education for Elementary School Students - Rasdi, Rasdi; Arifin, Ridwan; Widyawati, Anis; Adiyatma, Septhian Eka; Ilyasa, Raden Muhammad Arvy (The Indonesian Journal of International Clinical Legal Education, 2021)
Corruption is one of Indonesia’s biggest problems. Various efforts have been made not only in enforcement of corruption cases, but also in various preventive efforts. Kebumen Regency is one of the poorest districts in Central Java with a high rate of corruption among other city districts in Central Java. Several large-scale corruption cases also involved the Kebumen district government. Various attempts have been made, but anti-corruption attitudes must be encouraged. One of them is through various educational networks. The anti-corruption character strengthening program for students is the basic provision for the nation's next generation to not only eradicate corruption collectively but also have high integrity. This program is carried out at SDN Tlogodepok, Kebumen Regency where through this program an anti-corruption character will be formed for students as an anti-corruption fortress from an early age. This program will be implemented in several methods: (1) lectures and outreach, (2) anti-corruption games, (3) anti-corruption learning assistance, (4) initiation of honesty stalls, (5) formation of anti-corruption student cadres, and (6) establishment of an integrity zone at SDN Tlogodepok